Analysis and design of multiple element antennas for urban communication - Pontes, Juan (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2010)
This work focuses on the analysis and design of multiple element antennas (MEA) and their interaction with the propagation channel. In particular, attention is given to urban channels and how its information throughput, i.e. capacity, can be improved. With this in mind, this work extends an existing network model of the communication system in order to reduce computation time, investigates the communicational limits of MEA systems and proposes a synthesis method for capacity maximization.